Design of Short Peptides as Targeted Protein Inhibitors for Alzheimer’s Disease - Miksusanti Miksusanti; Faisal Razak; Nurul Huda; Muntasir Muntasir (Yayasan Adra Karima Hubbi, 2024)
Alzheimer's disease is a neurodegenerative disorder marked by cognitive decline and memory loss, primarily caused by the aggregation of amyloid-beta and tau proteins in the brain. Conventional treatments offer limited benefits, emphasizing the need for new therapeutic strategies. To design and evaluate short peptides as targeted protein inhibitors to prevent the aggregation of amyloid-beta and tau proteins, aiming to halt or reverse the progression of Alzheimer's disease. The study employed computational modeling to design peptides, followed by in vitro assays for initial screening, and in vivo tests using transgenic mouse models to assess therapeutic efficacy and safety. Techniques included mass spectrometry, HPLC, and behavioral tests for cognitive function. Designed peptides demonstrated high binding affinity and specificity for amyloid-beta and tau proteins, reducing aggregation by 70% in vitro. In vivo studies showed significant reductions in amyloid plaques and tau tangles, with improved cognitive performance in treated mice. Peptides effectively crossed the blood-brain barrier and accumulated in target brain regions. The findings support the potential of short peptides as a novel therapeutic approach for Alzheimer's disease, warranting further research and clinical trials to validate their efficacy and safety in human subjects.